Study on the effects of extreme climate and human activities on the growth mechanisms of Zostera japonica in the Yellow River estuary - Gao, Yanning; Chen, Kebing; Ma, Zixuan; Yi, Yujun (Frontiers in Marine Science, 2024)
Zostera japonica, as one of the major seagrasses in the Yellow River Estuary, plays a critical ecological role, particularly in providing habitat for marine organisms, stabilizing sediment, and contributing significantly to carbon sequestration. In recent years, Zostera japonica seagrass beds have receded extensively due to multiple impacts of natural factors and human activities. This study investigates the complex effects of extreme climate events and human activities on the growth mechanisms of Zostera japonica in the Yellow River Estuary using a combination of field sampling, laboratory analysis, and quantitative calculations. The result shows that there are significant differences in sediment characteristics between the north and south shores, with the south shore having finer sediments and higher nutrient content, which support more robust seagrass growth. The Water and Sediment Regulation Scheme (WSRS) dramatically alters water quality by reducing salinity and increasing turbidity, thus inhibiting photosynthesis and disrupting the physiological functions of Zostera japonica. Additionally, WSRS introduces an increase in heavy metals, which could potentially impact plant health and stress levels. Extreme weather events, particularly Super Typhoon Lekima, further compound these impacts by causing soil erosion, uprooting seagrass beds, and reducing biomass and seed production. The interplay of WSRS, climate change, and anthropogenic activities necessitates integrated management strategies to mitigate adverse effects and enhance habitat resilience. This study underscores the need for specific management strategies, such as controlling heavy metal inflows, implementing sediment stabilization techniques, and regulating freshwater discharge during key growth periods, to mitigate adverse effects and enhance habitat resilience for Zostera japonica in the Yellow River Estuary.